2015
DOI: 10.18632/oncotarget.3436
|View full text |Cite
|
Sign up to set email alerts
|

Flubendazole, FDA-approved anthelmintic, targets breast cancer stem-like cells

Abstract: Cancer stem-like cell (CS-like cell) is considered to be responsible for recurrence and drug resistance events in breast cancer, which makes it a potential target for novel cancer therapeutic strategy. The FDA approved flubendazole, has been widely used in the treatment of intestinal parasites. Here, we demonstrated a novel effect of flubendazole on breast CS-like cells. Flubendazole inhibited breast cancer cells proliferation in dose- and time-dependent manner and delayed tumor growth in xenograft models by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 52 publications
2
60
0
1
Order By: Relevance
“…For example, the E3 ligase Skp2, a critical factor in cell-cycle progression, restricted cancer progression and metastasis [63]. Flubendazole treatment arrests cells in the G2/M phase, suppresses CS-like cell migration, and induces breast cancer differentiation [65]. Here, we identified a novel function of EZH2 based on the finding that silencing EZH2 arrested CCS-like cells in the G1/S phase (Figure 7A-7B).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, the E3 ligase Skp2, a critical factor in cell-cycle progression, restricted cancer progression and metastasis [63]. Flubendazole treatment arrests cells in the G2/M phase, suppresses CS-like cell migration, and induces breast cancer differentiation [65]. Here, we identified a novel function of EZH2 based on the finding that silencing EZH2 arrested CCS-like cells in the G1/S phase (Figure 7A-7B).…”
Section: Discussionmentioning
confidence: 90%
“…This finding suggested that cycling CS-like cells are a target for eradicating cancer [62]. Indeed, accumulating studies have highlighted that arresting the cell cycle in CS-like cells decreases tumorigenesis [6365]. For example, the E3 ligase Skp2, a critical factor in cell-cycle progression, restricted cancer progression and metastasis [63].…”
Section: Discussionmentioning
confidence: 99%
“…Through transcriptome sequencing and extensive step-by-step in vitro analyses, we identified Cyclin D1 and snail1 as major downstream effectors of FRA-1, accounting for the CTHRC1-mediated regulation of proliferation and motility in ESCC cells. The most prominent function of snail1 in cancer cells is to induce the epithelial-mesenchymal transition (EMT) [46, 47], and it was recently reported that CTHRC1 upregulated snail1 to induce EMT by activating the Wnt/β-catenin signalling pathway in epithelial ovarian cancer [48]. Interestingly, we did not observe any meaningful alteration in β-catenin expression or in hallmarks of EMT [49], namely, E-Cadherin and vimentin, after CTHRC1 knockdown in ESCC cell lines (Additional file 5: Figure S3), suggesting that an alternative hypothesis is needed to explain findings for ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Similar antitumor activity of mebendazole was found in gastric cancer, medulloblastoma, glioblastoma, leukemia and myeloma as well as in breast cancer stem cell-like cells [22][23][24][25][26]. Mebendazole potently inhibited hedgehog (Hh) signaling and slowed the growth of Hh-driven human medulloblastoma cells at clinically attainable concentrations [27].…”
Section: Anticancer Activity Of Mebendazolementioning
confidence: 60%
“…Mebendazole can be administered with the non-steroidal anti-inflammatory drug sulindac for prevention of tumor initiation in a colon cancer model [33]. Colon Cancer [52] Breast Cancer Triple [29] Breast Cancer [53] Adrenocortical Cancer [19] Adrenocortical Cancer [39] Leukemia/Myeloma [25] Leukemia/Myeloma [34] Leukemia/Myeloma [59,64] NSCLC [20] NSCLC [36] Lung Cancer CSC [57] Cell Lines [9] Cancer stem cells [46] Cancer [61] Gastric Cancer [22] Osteosarcoma [37] Medulloblastoma [23] Prostate Cancer [36] Melanoma [21,29] Ovarian Cancer/ TICs [41 -44] Ovarian cancer [62] Breast CSC-like Cells [26] Breast CSC-like Cells [40] Breast CSC-like Cells [56] Glioblastoma [24,32] Glioblastoma [33] Glioblastoma CD133 + [60] This table lists reports on investigations employing mebendazole, niclosamide and pyrvinium (pamoate) as anticancer agents against cell lines or in experimental animal models.…”
Section: Anticancer Activity Of Mebendazolementioning
confidence: 99%